## Search This Blog

### Maths Puzzle

Maths Puzzle - 19 December

How can I get the answer 24 by only using the numbers 8,8,3,3.

You can use the main signs add, subtract multiply and divide.

1. The Answer comes in point (24.333...)!!

2. no 64/6 isn't 24

3. 8x8/3+3 is the answer easy

4. 8 x 3 = 24. The question doesn't say you must use all four numbers. Occam's Razor.

5. (8-3) / ((1/3) - (1/8)) = 24

6. 8+8=16
3+3=6
16+6=24

7. Bro 16+6 is 22 not 24

8. This comment has been removed by the author.

1. Steps-->

1.8/8=1
2.1+3=4
3.4*3!
4*6(since 3 factorial=6)
4.{[(8/8)+3]*3!}=24.☺

2. Steps-->

[(8/8)+3]*3!=24
since 3!=6☺

1. can't use factorial

2. CORRECT

ITS unacceptable

3. 24=8/(3-(8/3))=8/(1/3)=8*3=24

4. Root 8*8*3*3 = 8*3 = 24

5. chevireddyhemachandrareddyJuly 27, 2012 at 11:16 AM

8*8/3 + 3 =24

1. u have to use all the given no.s

6. 1. square root of 8 x square root of 8 = 8.

2. square root of 3 x square root of 3 = 3.

3. 8x3 = 24

1. i did not say u had to use all of them os 8x3=24

7. 8*(3*(3*3-8))=24 Ganesh

8. 8 square
3 square
by square root cancel square
then multiply
8*3=24

9. a=8;b=3
(a+b+ab)-1 gives right answer is 24

10. sq.root of (8*8)*sq.root of (3*3)
=8*3=24!what a silly sum!!!

11. sqrt(8+8) x (3+3) = 4x6 = 24

12. {8+{(8-3)}2}-(3)2=24
8+25_9=24
33-9=24

13. 8*3=24/3=8*3=24

14. (root(8,3)+root(8,3)!)
(2+2)! = 4! = 24

15. I is confused

17. 8 + 8 + Ɛ3
= 8+8+8
=24

18. 1. 8+8=16
2. 8-3=5
3. 3=3
So, (8+8)+(8-3)+3=24

19. sqrt(8x3) x sqrt(8x3)

20. cuberoot(8)*cuberoot(8)*(3+3)=24

21. 3x3x8/3=24

22. I have a better solution, 8×3=24! Nobody says you have to use all of them.......

23. Its so easy. Yous are bringing hard things when you could easily do this. :=: ( ( 8 - 3 ) x 3 ) + 8

24. sqrt(8^3÷8)*3

25. (square route of 8*8)*(square route of 3*3)= 8*3=24

26. 8+8=16
16/3
5.33*3=16
16+8=24

8/(3-8/3)

28. 1)8/(3-(8/3))
2)(8-3)!/(8-3)
3)[(8/8)+3]*3!
4)(∛8 × ∛8)!
5)√(8×8×3×3)
6)8+(8×(3!/3))
7)((√(8+8) × (3/3))!
8)√(8+8) × (3+3)
9)(log base(3!/3) of 8) × 8
10)((log base(3!/3) of (8+8))!

8/(3 - (8/3))
√(8*8*3*3)
(8-3)!/(8-3)
(3!*8/3) + 8
(3!/(³√8))*8
(3!*8) - (3*8)
8 + (3!/(3/8))
((³√8)*(³√8))!
(√(8+8))*(3+3)
(3 + (3*(8-8))!)!
(3!*8)/(8 - (3!))
(3 + ³√((8-8)!))!
((√(8+8))*3/3)!
(√(8*8))*(3!-3)
(3! - 3 + (8/8))!
(3 + (³√(8/8)))!
((³√8) + (³√8))!
(3! - 3 + ((8-8)!))!
(³√8^³√8)!
((8-(3!))*(8-(3!)))!
(((8-(3!))^(8-(3!)))!
38 -8 - (3!)
(8!!*3)/(3!*8)
(8-3)!/(8-3)
8*(3!)/³√8
[8*8/3]+3
(8 + √(8*3/3))!
3!*((8/8)+3)
3!*((8-8)!+3)
3*√((8^3)/8)